The ranging behavior of barn owl (Tyto alba javanica) translocated from paddy fields to urban areas - Ahmad Zabidi, Mohd Ezuddin Shah (2017)
The Barn Owl Tyto alba is common in most part of the world. There are 33 subspecies in all and protected in most countries. The particular sub species in Malaysia is T. alba javanica and is protected under the Wildlife Protection Act 1972 (Act 176) and the Environment Protection Act 2010. It has been encouraged to breed in artificial nest boxes provided in oil palm and rice field since it is an efficient predator rats. The idea of using the barn owl as a biological control of rats has recently been implemented in the city for the same purpose. Barn owls have been released in batches of two or three individuals in Subang Jaya has been observed to hunt and feeding well. The objective of study is to investigate the raging behaviour of barn owls in urban area. Female raptors are known for their territorial behaviour, maintaining an exclusive area around the nest box. Whereas male may range over an extensive area encompassing several nest boxes defended by females. Males may tolerate the presence of other males when food is abundant. These are the observations made in oil palm and rice field. The second objective is to estimate the home range and core area size of tyto alba. In this study, radio telemetry is employed to investigate the ranging pattern of males and females in the city, whereby the habitat make-up and nature is totally different than agricultural area where vegetation is the main attribute. At least three males and three females will be radio tagged and followed for at least three months, with a frequency of a total of seven nights of tracking every month. The difference between male and female home range pattern and area utilized will be analysed with BIOTAS, software which enable the calculations of range size of animals based on two different methods - Minimum Convex polygon (MCP) and the kernel method. It is projected that the pattern of home range used and size would be comparable with studies previously conducted in agricultural land and open fields.